Beowulf, the wrath of God and the fall of the angels - Leneghan, F (Taylor & Francis, 2024)
This article argues that Beowulf’s anger is not only a form of furor heroicus but also a manifestation of the wrath of God. Through comparison with Genesis A and other Old English biblical poems, as well as biblical and apocryphal sources, the article identifies the Fall of the Angels as an important context for Beowulf’s first two monster-fights. Countering arguments that Beowulf is a flawed or even failed hero, I propose that when read in the light of Old English biblical poetry, Beowulf emerges not as a doomed pagan or frenzied berserker but as a righteous avenger whose anger is controlled and directed against evil.